Metabolic pathway for degradation of 2-chloro-4-aminophenol by Arthrobacter sp. SPG - Arora, Pankaj Kumar (Microb Cell Fact, 2014)
A degradation pathway of 2-chloro-4-aminophenol (2C4AP) was studied in an Arthrobacter sp. SPG that utilized 2C4AP as its sole source of carbon and energy. The 2C4AP degradation was initiated by a 2C4AP-deaminase that catalyzed the conversion of 2C4AP into chlorohydroquinone (CHQ) with removal of ammonium ion. In the next step, a CHQ-dehalogenase dehalogenated CHQ to hydroquinone (HQ) that cleaved into γ-hydroxymuconic semialdehyde by a HQ-dioxygenase. The 2C4AP degradation was also investigated in sterile and non-sterile soil microcosms using strain SPG. The results show that the SPG cells degraded 2C4AP more rapidly in sterile soil than non-sterile soil. Our studies showed that strain SPG may be used for bioremediation of 2C4AP-contaminated sites. This is the first report of the 2C4AP degradation by any bacteria.